New taxa of Cryphocricinae (Heteroptera: Naucoridae) from the Guiana Shield: Hygropetrocoris Sites, n. gen. and two new species of Ambrysus Stål - Sites, Robert W. (Zootaxa, 2015)
A new genus and species of Naucoridae are described from two male specimens that inhabited an algae-covered granite rock seep in Guyana. Hygropetrocoris Sites NEW GENUS is diagnosed by a nearly vertical and apparently freely movable head, bulbous eyes, hair lines and hair patches on the hemelytra, profemur with anterior excavation that can receive a prominent tooth on the opposable protibia, and stout marginal tufts of setae on the pronotum, embolium, and connexiva. H. guyana Sites NEW SPECIES is further diagnosed by pseudoparameres that are wide, black, directed posterolaterally, and bluntly produced laterally. Character states of this genus are compared with those of the other genera of Cryphocricinae. Two new species of Ambrysus Stål from the region also are described. Ambrysus brunneus Sites NEW SPECIES is described from a single female specimen and diagnosed by a digitate lobe on laterosternite VI, shape of the subgenital plate, and concolorous dark brown dorsal coloration; Ambrysus shorti Sites NEW SPECIES is described from a single male specimen and diagnosed by its small size, narrow body form, and tentacular setae of the parameres.